HARMONIZATION OF HISTORICAL DATA AND EXPERT MODELS FOR FORECASTING DEMAND FOR RAIL TRANSPORTATION - A. Zamkovoy; S. Kudiyarov; R. Martyshkin; V. Strizhov (Вестник университета)
The problem of rail freight traffic volume forecasts using retrospective data, analysis of the impact of external factors on the cargo base and the distribution of goods shipments by transport mode is solved. In order to improve the forecast fidelity proposed the model integrating historical data of freight rail traffic volume and expert assessments of external factors affecting the work of rail transport hasbeen proposed. The structure of historical data, time series of freight traffic volumes, as well as relationship with expert models is described.